Empowering UP Level MSMEs: The Role of Integrating Government Support, Strengthening Legality, and Market Access through the Upgrade Assistance Program - Hariroh, Fiqih Maria Rabiatul; Rahmiati, Filda; Sandi, Prasetyo Hari; Bairuroh, Ickbal Hofifi (Almana : Jurnal Manajemen dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the Indonesian economy, as they can absorb a large workforce and contribute significantly to the Gross Domestic Product (GDP). However, many MSMEs still face significant challenges, particularly regarding legal aspects, lack of market access, and inefficient business management. This study aims to evaluate the impact of government support, business legitimacy, and market access on improving the level of Micro, Small, and Medium Enterprises (MSMEs) in Bekasi Regency. This study employs a quantitative approach using a survey method involving 120 micro, small, and medium enterprise (MSME) actors participating in a capacity-building program. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The research findings indicate that government assistance has a positive and significant impact on improving the level of Micro, Small, and Medium Enterprises (MSMEs). Similarly, access to the market has been proven to have a significant positive impact on the advancement of MSMEs. Conversely, business legitimacy does not have a significant impact on increasing MSME levels.